Hubungan antara Metode Demonstrasi dan Metode Praktik dengan Hasil Pencapaian Keterampilan pada Kegiatan Ekstrakurikuler Pramuka - Putri, Rafinda; Jamna, Jamaris (Penerbit Aksara Rentaka Siar (ARS), 2019)
This research was motivated by the success of scout extracurricular activities at Bukittinggi Middle School 1. This is thought to be due to the learning method used by the trainer. The study aims to see the successful achievement of skill in scout extracurricular activities at Bukittinggi middle school 1 seen from the use of demonstration methods and practice methods. This type of research is correlational quantitative research, the population in this study were 45 scout members. Sampling used cluster random sampling so the sample was taken as many as 34 people. Data collection techniques use questionnaires while data collection tools use a list of statements (questionnaire). Data analysis techniques use product-moment formula. The results of this study indicate that (1) ratio demonstration methods in scout extracurricular activities from the aspect of action are classified as high, (2) demonstration methods in scout extracurricular activities from the illustration aspect are high,(3) demonstration method in scout extracurricular activities from the demonstration aspect are high, (4) demonstration methods in scout extracurricular activities from the aspect of oral statements are classified as high, (5) practice methods in scout extracurricular activities in dexterity are hight, (6) practice methods in scout extracurricular activities are high, (7) practice methods in scout extracurricular activities from the aspect of accuracy classified as high, and (8) the practice method in scout extracurricular activities from the aspect of opportunity is high.